DESIGN AND MAKING OF INDUSTRY 4.0 READINESS MEASUREMENT TOOL FOR INDUSTRY IN INDONESIA - Caesar Ananta, Kevin
valuat ion of Industry 4.0 readiness is an important thing to do to understand the posit ion of a company in the process of adapting the Industry 4.0 concept. To do this, a measuring tool that is able to measure the current condit ion of a company and indicate what must be applied or developed to achieve the expected Industry 4.0 applicat ion is needed. This study aims to design and create an Industry 4.0 readiness measurement tool, commonly known as Industry 4.0 Readiness Index, that is able to measure the condit ion of Indonesian companies thoroughly. The stages of research carried out started with the literature study on Industry 4.0 concept, determinings the core concepts to form an understanding of Industry 4.0, deriving parameters and indicators based on the needs of the application of Industry 4.0, and evaluat ion and wight determinat ion on the derived parameters. In the final stage of the research testing of the instruments is carried out through case studies of real condit ions of several manufacturing industry companies in Indonesia. The output of this study is a set of measurement tool that is able to evaluate state of a company in the process of adapting the Industry 4.0 concept accurately. The measurement result of a company's state is also presented in quantitative form of indexes ranging from zero to six to six.